2012
DOI: 10.1128/jb.00337-12
|View full text |Cite
|
Sign up to set email alerts
|

Development of Competence for Genetic Transformation of Streptococcus mutans in a Chemically Defined Medium

Abstract: c Streptococcus mutans develops competence for genetic transformation in response to regulatory circuits that sense at least two peptide pheromones. One peptide, known as CSP, is sensed by a two-component signal transduction system through a membrane receptor, ComD. The other, derived from the primary translation product ComS, is thought to be sensed by an intracellular receptor, ComR, after uptake by oligopeptide permease. To allow study of this process in a medium that does not itself contain peptides, devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(149 citation statements)
references
References 34 publications
6
139
4
Order By: Relevance
“…Interestingly, the cultivation medium controls which of those two circuits is activated: XIP is only active in a peptidefree medium; it has been suggested that peptides might block the Opp transporter required for import of the active XIP heptamer . Conversely, CSP works only in a peptide-rich medium-here it has been suggested that the membrane-bound HtrA enzyme, which can degrade CSP, must be saturated by peptides to reduce CSP degradation (Desai et al, 2012;Federle and Morrison, 2012). In addition, it has been shown for S. thermophilus that the ComR response regulator is tolerant to small changes in the sequence of XIP and can even be activated by hydrolysis products of casein, that is, octapeptides present in the medium (Fontaine et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cultivation medium controls which of those two circuits is activated: XIP is only active in a peptidefree medium; it has been suggested that peptides might block the Opp transporter required for import of the active XIP heptamer . Conversely, CSP works only in a peptide-rich medium-here it has been suggested that the membrane-bound HtrA enzyme, which can degrade CSP, must be saturated by peptides to reduce CSP degradation (Desai et al, 2012;Federle and Morrison, 2012). In addition, it has been shown for S. thermophilus that the ComR response regulator is tolerant to small changes in the sequence of XIP and can even be activated by hydrolysis products of casein, that is, octapeptides present in the medium (Fontaine et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The comS encodes the XIP precursor is processed to mature and internalize the cells through the transporter, Opp/Ami. The mature signal in-turn interacts with the comR and activate the gene comX to express the factor, r x [36,37]. Recent data has shown a drastic reduction of XIP levels in the comX (r x ) deficient S. mutans strains, as it evidence the positive feed-back role of ComX in ComRS/XIP expression where its binding sites were localized either within or upstream of ComRS [38].…”
Section: S Mutans and Dental Cariesmentioning
confidence: 99%
“…Syvitski et al [29] reported that the C-terminal truncated CSP peptides could competitively affect the QS activity and the structural motif in the C-terminal domain restores the activation of the QS signal transduction pathway [34,35]. Further the mutational studies (Point deletion) revealed the loss of function of CSP in promoting genetic competence without affecting the binding of peptide to the receptor [34][35][36][37].…”
Section: S Mutans and Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…This missing link has been recently filled by the discovery of a type II ComRS signaling system that proximally induces transcription of comX in Streptococcus mutans in response to signal peptide XIP [5,6]. When Streptococcus mutans is grown in CDM, competence activation through the ComRS system is superior, nearly involving the entire population [5,16]. However, XIP appears to be inactive when Streptococcus mutans is grown in a complex medium [5,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%